Bobtail® bolt preload loss in wind turbine tower prototype: Hammerstein‐Wiener identification model. (13th September 2017) - Mohammadi, Mohammad Reza Shah; Matos, Rui; Rebelo, Carlos
ABSTRACT: Nowadays the wind turbines with the high power capacity are installed for the onshore wind parks. In order to achieve higher wind speeds and more stable wind, wind turbine towers are designed for higher altitude. Moreover, higher altitude reduces turbulence and wind shear induced vibrations. The convectional tubular towers are assembled using welded ring flanged joints. Moreover, preloaded bolts are used to connect the segments' flanges together. Therefore, the fatigue problem is predominant in the tall towers and fatigue failure due to welded connection and/or due to the bolts in tension may be the governing design situation. To tackle the fatigue problem in the bolted joints and discard the welded connections, a new friction connection is designed for tubular segment assembly. The tower segments are designed with long open slotted holes. The preloaded bolts are used to provide contact between the slotted holes and the intermediate auxiliary plate. Therefore, the connection will resist only by the friction in between the plates. In order to provide necessary friction between the plates, sufficient pre‐load should be applied on the bolts. Moreover, it should be guaranteed that the load loss in the bolts is trivial. Therefore, Bobtail® bolt as free maintenance preloaded bolts are used in the friction connections. This paper deals with the identification of a function for bolts load loss behavior in the friction connections and provide an estimation for lifetime loss. A monitoring setup has been settle to measure the load in the bolts and the environmental temperature simultaneously for almost a year. Consequently, the Hammerstein‐Weiner method, was applied to create the nonlinear dynamic model of the friction connection preloading behavior regarding the environmental temperature variation. Furthermore, the identified function output for the measured temperature was compared with the measured force and then the error was calculated. Based on the model, the load loss for constant temperature was calculated for the period of the measurement and was estimated for 20 years of life time span of the structure. The findings demonstrated acceptable amount of load loss in a year and estimation showed that bolts loads retain constant pre‐load after a two years period. Moreover, it is obtained the initial fastening conditions were important to achieve free‐maintenance bolts.